Tindak Tutur Ilokusi Ekspresif dr. Tirta pada Podcast Malaka - Sistyani Putri Utami; Eko Suroso; Eko Muharudin; Laily Nurlina (Kopula: Jurnal Bahasa, Sastra, dan Pendidikan, 2026)
This study discusses the expressive illocutionary speech acts used by Dr. Tirta in the Malaka podcast entitled "Just Graduated, Do You Want to Open a Business?". This study is motivated by the importance of understanding the use of expressive illocutionary speech acts in digital media that can influence people's perspectives, especially the younger generation. So far, research on speech acts has focused more on the context of formal education and daily life, while on business motivation podcasts is still relatively limited. The purpose of this study is to describe the form and function of expressive illocutionary speech acts used by Dr. Tirta in the Malaka Podcast. This study uses a qualitative descriptive method with a pragmatic approach. The research data in the form of Dr. Tirta's utterances which are forms of expressive illocutionary speech acts, were obtained through listening and note-taking techniques. Data analysis was carried out by identifying the forms of acts and utterances, classifying the types of acts and utterances, and then interpreting their pragmatic functions. The results of the study show that the dominant expressive illocutionary speech acts include criticism, sarcasm, support, praise, and expressions of concern. These speech acts are used to convey motivation, build social awareness, and influence listeners' mindsets regarding education and the world of work. This study concludes that Dr. Tirta's use of expressive illocutionary acts in the Malaka podcast can be used as an effective communication strategy in conveying motivational messages clearly and persuasively.